Association between sleep and weight loss in a 12-month digital lifestyle intervention - Ahola, Aila J.; Joki, Anu; Venäläinen, Mikko S.; Kupila, Sakris K.E.; Suojanen, Laura-Unnukka; Paavonen, E. Juulia; Pietiläinen, Kirsi H. (Elsevier BV, 2026)
Objectives: We studied how sleep quality and chronotype relate to weight loss in a 12-month real-world digital lifestyle intervention, the Healthy Weight Coaching.
Methods: Patients self-reported weight and waist circumference and completed a set of customized sleep-related online questionnaires at baseline, 3-, 6-, 9-, and 12-months. Primary outcomes were percent changes in weight and waist circumference, calculated from baseline to each follow-up time point. Using generalized linear regression for repeated measures, we explored associations between sleep variables (individual variables and factor analysis-derived clusters) and changes in measures of obesity across the program. Additionally, we investigated how changes in reported sleep are associated with weight loss outcomes.
Results: Baseline data included 1883 individuals (82.6 % women, median age 52 years, median BMI 39.1 kg/m2). Reporting sleep apnoea was associated with less successful weight loss across the program [weight, B = 0.760 (95 % CI = 0.446–1.073), p < 0.001; waist, B = 1.275 (95 % CI = 0.780–1.771), p < 0.001]. Eveningness and Tiredness factors were associated with poorer weight [B = 0.206 (95 % CI = 0.027–0.385), p = 0.024 and B = 0.613 (95 % CI = 0.371–0.855), p < 0.001, respectively] and waist circumference [B = 0.434 (95 % CI = 0.155–0.713), p = 0.002 and B = 0.720 (95 % CI = 0.337–1.102), p < 0.001, respectively] reduction over the 12-month program. Increase in reported daytime alertness, over the program, was beneficial for weight loss outcomes.
Conclusions: Addressing evening chronotype and reasons for reduced daytime alertness may be associated with enhanced weight loss; however this study does not establish causality. Additional research is needed to adapt interventions for those with sleep apnoea.
Trial registration: The trial is registered at clinicaltrials.cov (Clinical Trials Identifier NCT04019249).